The Internal Aspects of Change on Language Used by Digital Native in Facebook Status Update - Hasan Aif, Ramli; Soeparto, Soeparto (University of Muhammadiyah Malang, 2014)
The Internal Aspects of Change on Language Used by Digital Native in Facebook Status Update